Fast soil recovery after a fire: case study in Maritime Alps (Piedmont, Italy) using microarthropods and QBS-ar index - Fusco, Tommaso; Fortini, Lorenzo; Casale, Francesca; Jacomini, Carlo; Di Giulio, Andrea (Frontiers in Ecology and Evolution, 2024)
Soil is a very fragile ecosystem, often subject to many threats. Wildfires can affect edaphic communities depending on the intensity and seasonality of the fire. Different groups of soil fauna tend to respond differently to this type of disturbance, but the lack of data prevents to fully analyze the impact of fire. Soil microarthropods show a particular sensitivity to disturbances of different nature, making them excellent biological indicators. That is why in recent years many biotic indices to assess soil quality, like QBS-ar (Soil Biological Quality based on arthropods), have been developed. The objective of this study was to evaluate whether there might be a significant difference between areas affected or not by fire in the locality of Andonno (Piedmont, Italy) in terms of QBS-ar values, 18 years after this disturbance, and whether the reforestation intervention is having a positive effect on soil quality. Two sampling sites were selected within the sampling area and in each, six soil samples were taken. Microarthropods were extracted with a Berlese-Tüllgren extractor and soil biological quality was calculated using the QBS-ar index. No significant difference in QBS-ar values were found between the fire burned and unburned areas (p=0.37). The number of biological and euedaphic forms in the two sites was similar. It appears that microarthropod communities manage to recover in a short time, indicating that in the study area soil fauna has shown a fast recovery after extreme events like wildfires.